Effect of Condensed Tannin of Leucaena and Calliandra Leaves in Protein Trash Fish Silage on In vItro Ruminal Fermentation, Microbial Protein Synthesis and Digestibility - Rimbawanto, Efka Aris; Yusiati, Lies Mira; Baliarti, Endang; Utomo, Ristianto (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2015)
Two plants as condensed tannin (CT) sources were supplemented to protein trash fish silage (TFS) to observe their effect on in vitro ruminal fermentation product, micobial protein synthesis, and Â Â digestibility. CT supplementation on protein trash fish silage was on control proportion (0), under optimum level (2.0%), at optimum level (4.0%), and above optimum level (6.0%) of g TFS); of protein precipitation of bovine serum albumin (BSA) with CT from L. leucocephala; and under optimum level (1.5%), at optimum level (3.0%) and above optimum level (4.5% of g TFS), BSA protein precipitation with CT from C. calothyrsus. The effect on degradation in ruminal fluid and ruminal fluid followed by incubation in HCl-pepsin was evaluated using a modified two-step in vitro method. The CT level of L. leucocephala and C. calothyrsus was 4% and 6%, respectively with protein precipitation BSA was 26.25 and 31.77 g BSA/g CT, respectively. CT supplementation to trash fish silage, ruminal fermentation product (NH3-N, C2, C3, and total VFAs) and digestibility (DM and OM) decreased (P<0.01) and increased (P<0.01) total CP digestibility (in HCl-pepsin). The difference was attributed to CT source without affecting ruminal microbial protein synthesis. CT of L. leucocephala was better in increasing total protein digestibility (70%) than that of C. calothyrsus Â (15%). It indicated that CT of C. calothyrsus was less effective in protected TSF protein degradation in rumen compared to that of L. leucocephala.